The problem of adapting existing residential buildings in the country to the requirements of ecology = Problem dostosowania istniejących budynków mieszkalnych na wsi do wymogów ekologicznych - Dąbkowski, Norbert; Pędzich, Bożena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of direct research on residential buildings and their modernization in selected ecological farms of the Mazovia region. The research area covered two poviats (counties) in the Mazowieckie Voivodeship: Makowski and Ostrołęcki. A total of 10 residential buildings on farms were examined. The study was conducted based on conversations with owners during on site visits.
Keywords: budynek mieszkalny; modernizacja; remonty; ekologia; residential building; modernization; renovation; ecology